(untitled) (Al-Mansour Journal, 2025)
With the fast deployment of Internet of Things (IoT) in healthcare environment, it is critically important to secure reliable mechanisms for securing constantly streamed real-time data. This paper suggests a blockchain-based architectural model to preserve C-I-A (Confidentiality, Integrity and Availability) of health data while transferring from IoT-Devices. The model creates a simulated blockchain network on the MATLAB on which it incorporates Delegated Proof-of-Stake (DPoS) consensus protocol, PoW and PoV mechanisms to strengthen transactional trust and eliminate unauthorized data fabrication. In the simulation, different testing parameters (node density, amount of data traffic, and network change rate) are set up to test the system performance. We analyze the efficiency of the framework to enable continuous data transfers and balance real-time computational offloading in healthcare IoT environments. The results indicate that the architecture can support continuous secure and trustworthy information flows that are available, making critical healthcare data authentic and resilient